Consolidation and Maintenance in Newly Diagnosed Multiple Myeloma. Issue 32 (10th November 2021) - Sonneveld, Pieter; Dimopoulos, Meletios A.; Beksac, Meral; van der Holt, Bronno; Aquino, Sara; Ludwig, Heinz; Zweegman, Sonja; Zander, Thilo; Zamagni, Elena; Wester, Ruth; Hajek, Roman; Pantani, Lucia; et al.
Abstract : PURPOSE: To address the role of consolidation treatment for newly diagnosed, transplant eligible patients with multiple myeloma in a controlled clinical trial. PATIENTS AND METHODS: The EMN02/HOVON95 trial compared consolidation treatment with two cycles of bortezomib, lenalidomide, and dexamethasone (VRD) or no consolidation after induction and intensification therapy, followed by continuous lenalidomide maintenance. Primary study end point was progression-free survival (PFS). RESULTS: Eight hundred seventy-eight eligible patients were randomly assigned to receive VRD consolidation (451 patients) or no consolidation (427 patients). At a median follow-up of 74.8 months, median PFS with adjustment for pretreatment was prolonged in patients randomly assigned to VRD consolidation (59.3 v 42.9 months, hazard ratio [HR] = 0.81; 95% CI, 0.68 to 0.96; P = .016). The PFS benefit was observed across most predefined subgroups, including revised International Staging System (ISS) stage, cytogenetics, and prior treatment. Revised ISS3 stage (HR, 2.00; 95% CI, 1.41 to 2.86) and ampl1q (HR, 1.67; 95% CI, 1.37 to 2.04) were significant adverse prognostic factors. The median duration of maintenance was 33 months (interquartile range 13-86 months). Response ≥ complete response (CR) after consolidation versus no consolidation before start of maintenance was 34% versus 18%, respectively ( P < .001). Response ≥ CR on protocol including maintenance was 59% with consolidation and 46% without ( P < .001). Minimal residual disease analysis by flow cytometry in a subgroup of 226 patients with CR or stringent complete response or very good partial response before start of maintenance demonstrated a 74% minimal residual disease–negativity rate in VRD-treated patients. Toxicity from VRD was acceptable and manageable. CONCLUSION: Consolidation treatment with VRD followed by lenalidomide maintenance improves PFS and depth of response in newly diagnosed patients with multiple myeloma as compared to maintenance alone.